Seasonal clustering in inflammatory bowel disease: a single centre experience. (August 2015) - Basaranoglu, Metin; Sayilir, Abdurrahim; Demirbag, Ali E; Mathew, Sanju; Ala, Aftab; Senturk, Hakan
<x xml:space="preserve">Abstract</x> Backgrounds and aims: External stimuli are considered as possible triggers for the onset of inflammatory bowel disease (IBD), and particularly chronic ulcerative colitis (CUC) in genetically susceptible individuals. Our aims were to investigate monthly clustering-patterns in the onset of symptoms and diagnosis of IBD, as well as health seeking behavior in those individuals. Materials and methods: Two hundred and eighty-two consecutive patients with IBD were included. Onset of symptoms (month) and delay to diagnosis were analyzed. Kruskal–Wallis and Roger's test were used to analyze for statistical patterns in seasonal clustering. Results: There were 181 males and 101 females with IBD; mean age: 40 ± 14.7 years (median: 38, range: 14–79 years). The peak number of IBD cases was seen in winter/early spring, with the lowest numbers in autumn, which reached statistical significance in the CUC group (p: 0.029). Seasonal changes were not significantly affected by gender. The time delay to diagnosis from symptom onset was 3.0 ± 2.3 months in males (median: 2, range: 0–12 months) vs 3.2 ± 3.2 months (median: 2, range: 0–18 months) in females (not statistically significant). Conclusion: Our results show a seasonal relation in IBD cases, particularly in CUC, which may suggest external stimuli acting as a precipitant to IBD in susceptible individuals. There was a delay between symptom onset and CUC diagnosis, which was not felt to be clinically significant.